Changes in strength, power, and steroid hormones during a professional Rugby Union Competition - Argus, C. K.; Gill, N. D.; Keogh, J. W. L.; Hopkins, W. G.; Beaven, C. M. (The Journal of Strength and Conditioning Research, 2009)
The purpose of this investigation was to assess changes in strength, power, and levels of testosterone and cortisol over a 13-week elite competitive rugby union season. Thirty-two professional rugby union athletes from a Super 14 rugby team (age, 24.4 ± 2.7 years; height, 184.7 ± 6.2 cm; mass, 104.0 ± 11.2 kg; mean ± SD) were assessed for upper-body and lower-body strength (bench press and box squat, respectively) and power (bench throw and jump squat, respectively) up to 5 times throughout the competitive season. Salivary testosterone and cortisol samples, along with ratings of perceived soreness and tiredness, were also obtained before each power assessment. An effect size of 0.2 was interpreted as the smallest worthwhile change. A small increase in lower-body strength was observed over the study period (8.5%; 90% confidence limits ±7.2%), whereas upper-body strength was maintained (-1.2%; ±2.7%). Decreases in lower-body power (-3.3%; ±5.5%) and upper-body power (-3.4; ±4.9%) were small and trivial. There were moderate increases in testosterone (54%; ±27%) and cortisol (97%; ±51%) over the competitive season, and the testosterone to cortisol ratio showed a small decline (22%; ±25%), whereas changes in perceived soreness and tiredness were trivial. Individual differences over the competitive season for all measures were mostly trivial or inestimable. Some small to moderate relationships were observed between strength and power; however, relationships between hormonal concentrations and performance were mainly trivial but unclear. Positive adaptation in strength and power may be primarily affected by cumulative training volume and stimulus over a competitive season. Greater than 2 resistance sessions per week may be needed to improve strength and power in elite rugby union athletes during a competitive season.